RADIOGRAPHIC EVALUATION OF GONIAL ANGLE (BY USING PANORAMIC AND LATERAL CEPHALOMETRIC RADIOGRAPHS) (World Bulletin of Public Health, 2022)
The outside gonial Angle is a significant Angle in the orthodontic treatment and in the craniofacial complex . Because of superimposed pictures of the anatomical structure including gonial angle in lateral cephalometric so we used Panoramic radiograph to measure the gonial Angle ((left and right)) accurately without superimposed that present in cephalometric .
Keywords: Gonial Angle; Radiography; Panoramic; Cephalometry